THE EFFECT OF GIVING AMINO ACID LYSINE AND METHIONINE THROUGH WATER ON THE QUALITY OF ISA BROWN CHICKEN EGGS THAT ARE STORED FOR FOUR WEEKS - D A. P., Widnyani; D A. P., Widnyani; Mahardika, I G.; Astawa, I P. A. (Jurnal Peternakan Tropika, 2021)
This research was conducted to determine the effect of the administration of amino acids lysine and methionine through drinking water on the quality of eggs stored for 4 weeks. The research was conducted  in Candikusuma Village, Melaya District, Jembrana Regency, Bali Province for 4 months. The completly randomized design were used in this experiment with four treatments (P0, P1, P2, and P3). P0: Chickens given drinking water without lysine and methionine. Q1: Chickens given drinking water added 0.1 % lysine and methionine. Q2: Chickens given drinking water added 0.15% lysine and methionine. Q3: Chickens given drinking water added 0.2% lysine and methionine. Each treatment is repeated 4 times so that there are 16 experimental units. The observed variables are the   weight of the egg, the weight of the egg type, the index of the yolk, the color of the yolk, and the haugh value of the egg unit.   The results showed no  effect of lysine and methionine on egg yolk index, but had an effect on egg weight, egg type weight, egg yolk color and  haugh unit. Key words : lysine, methionine, egg quality, and Isa Brown chicken